Peritumoral MRI findings and brain herniations in epileptic dogs with prosencephalic brain tumors: a multicentre retrospective study - Tabbì, Marco; Fugazzotto, Domenico; Caterino, Chiara; Minniti, Simone; Toneatti, Valeria; Barillaro, Giuseppe; Minato, Simone; Giannetto, Claudia; Fatone, Gerardo; Macrì, Francesco (Frontiers in Veterinary Science, 2025)
Prosencephalic brain tumors (PBTs) are frequently associated with epileptic seizure in dogs, yet the incidence and characteristics of brain herniations (BHs) in this context remain poorly described. This multicentre retrospective study aimed to evaluate the incidence and distribution of BHs and other associated MRI findings in 80 dogs presenting with epileptic seizures secondary to PBTs. MRI studies were assessed for peritumoral edema, lateral ventricular compression, midline shift (MS), subfalcine herniation (SH), caudal transtentorial herniation (CTH), foramen magnum herniation (FMH), and displacement of the quadrigeminal lamina (DQL). Peritumoral edema and lateral ventricular compression were observed in 85 and 77.5% of cases, respectively. MS was observed in 87.5% of cases. SH and CTH were the most common BHs, present in over 75 and 31% of cases, respectively. DQL was observed in 57% of cases, including dogs with tumors anatomically distant from the midbrain. Although tumor volume did not significantly differ between groups, larger lesions were positively correlated with the presence of edema, lateral ventricular compression and laminar displacement. These findings demonstrate that MRI features reflecting mass effect—particularly peritumoral edema, MS, and specific types of BHs—are highly prevalent in dogs with seizure-associated PBTs and may contribute to epileptic seizures generation. The MRI features identified in this study may have prognostic value for potential epileptic seizures development, and should therefore be considered during the clinical evaluation of affected dogs.